(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
One form of tourism development in Rendeng Village, Malo District, and Bojonegoro Regency is educational and pottery tourism, which is usually called Wisata Edukasi Gerabah (WEG). This tourism emerged on the initiative of the local youth organization, Karang Taruna, who saw the community’s potential as pottery craftsmen. The resulting pottery has a distinctive character and uniqueness, taking ideas from the shapes of household utensils and other interior elements, with a distinctive paint color. The COVID pandemic has caused this pottery educational tourism to experience ups and downs, so pottery craftsmen and WEG managers are trying to revive this activity as optimally as possible. Considering that this activity can increase the income and economic value of the community, especially for pottery craftsmen. Resilience means the ability of a group or community to overcome disturbances resulting from social, political, and environmental change. The level of social capability of the community is expected to create a better environment and more sustainable. The purpose of this study is to study the dynamics of community resilience in managing pottery educational tourism, especially after the COVID pandemic that occurred some time ago, so that it continues to exist and is even able to grow and develop to support sustainability. This research is included in the qualitative type, with a phenomenological approach. Data collection methods are carried out through observation and interviews. While data analysis uses the SWOT technique, factors are obtained that can be strengths, weaknesses, opportunities, and threats to being able to survive. The results of this study indicate that pottery educational tourism has the ability to survive so that it continues to exist, supporting sustainability.